Turn, turn, turn: A digital history of German historiography, 1950-2019 - Lino Wehrheim; Tobias Alexander Jopp; Mark Spoerer (Humboldt University Berlin, 2021)
The increasing availability of digital text collections and the corresponding establishment of methods for computer-assisted analysis open up completely new perspectives on historical textual sources. In this paper, we use the possibilities of text mining to investigate the history of German historiography. The aim of the paper is to use topic models, i.e. methods of automated content analysis, to explore publication trends within German historiography since the end of World War II and, thus, to gain data-based insights into the history of the discipline. For this purpose, we evaluate a text corpus consisting of more than 9,000 articles from eleven leading historiographical journals. The following questions are addressed: (1) Which research subjects mattered, and in how far did this change over time? (2) In how far does this change reflect historiographical paradigm shifts, or 'turns'? (3) Do the data allow to map the emergence of these turns, i.e., can we periodize/historicize them? (4) Which of the proclaimed turns mattered in the sense that it is actually reflected in the research themes we find, and which turn does not?
urn:nbn:de:kobv:11-110-18452/23508-1
Keywords: B40; N01; 330; German historiography; cultural turn; digital history; topic modelling